2017
DOI: 10.1039/c7cp01500c
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the ionic fingerprints of molecular monolayers

Abstract: We have previously proposed, and experimentally resolved, an ionic charge relaxation model for redox inactive self-assembled monolayers (SAMs) on metallic electrodes in contact with a liquid electrolyte. Here we analyse, by capacitance spectroscopy, the resistance and capacitance terms presented by a range of thiolated molecular films. Molecular dynamics simulations support a SAM-specific energy barrier to solution-phase ions. Once surmounted, the entrapped ions support a film embedded ionic capacitance and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 52 publications
0
40
0
Order By: Relevance
“…47,48 Traditionally, non-faradaic capacitive ion sensing has been interpreted by solely considering perturbations of a conventional double layer. 49 This is a rather simplistic and incomplete picture and, furthermore, in the presence of moderately dense molecular films (see above), double layer effects are much reduced 36,39 and the measured capacitance C t , though still dominated by the Debye 'electrostatics', as discussed in the preceding sections, includes film characteristics itself, such as those related to non-specific ionic ingress. 36,39 In an analysis of designed ion sensors we have shown that a modulation of C m i , an ion binding specific form of C t , (Fig.…”
Section: Ionic Capacitive Sensorsmentioning
confidence: 97%
See 4 more Smart Citations
“…47,48 Traditionally, non-faradaic capacitive ion sensing has been interpreted by solely considering perturbations of a conventional double layer. 49 This is a rather simplistic and incomplete picture and, furthermore, in the presence of moderately dense molecular films (see above), double layer effects are much reduced 36,39 and the measured capacitance C t , though still dominated by the Debye 'electrostatics', as discussed in the preceding sections, includes film characteristics itself, such as those related to non-specific ionic ingress. 36,39 In an analysis of designed ion sensors we have shown that a modulation of C m i , an ion binding specific form of C t , (Fig.…”
Section: Ionic Capacitive Sensorsmentioning
confidence: 97%
“…If one presents an electrode-surface-confined and electrolyteexposed molecule with an applied potential, V, and there exists no redox activity at V, then one would expect (only) a field driven ionic ingress. 36 This can be monitored through both the resistance and capacitance of the film 37,38 (which in this case is primarily ionic in nature) as measured by IS. To understand how the above discussed concepts of charge conductance G and C m apply here, we need to consider eqn (2) under such (ionic charging) conditions.…”
Section: The Electrochemistry Of Non-faradaic Molecular Filmsmentioning
confidence: 99%
See 3 more Smart Citations